PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS, RISIKO OPERASIONAL TERHADAP PROFITABILITAS (PADA PT. BPR. MAHA BHOGA MARGA) - I Made Rai Sugiartha; Ni Luh Sili Antari; I Putu Santika (Universitas Triatma Mulya, 2021)
This study was conducted to re-examine the effect of the level of banking risk on profitability at PT. BPR. Maha Bhoga Marga by using several variables namely Credit Risk or Non Performing Loan (NPL), Liquidity or Loan to Deposit Ratio (LDR), and Operational Risk or BOPO to Profitability or Return on Assets (ROA). Profitability is the company's ability to earn profits or the effectiveness of the company's management so that the company can find out how much profit can be obtained in a certain period. Profitability can also be used as a measure of the company's level of efficiency in tackling company risk. So that PT. BPR. Maha Bhoga Marga can use the existing findings as material to evaluate its performance and suggestions in the findings in this study, so that PT. BPR. Maha Bhoga Marga is able to develop and improve its business expansion in the future. The data obtained are secondary data obtained based on the annual publication report of PT. BPR. Maha Bhoga Marga for the period from 2014 to 2018. The analysis technique used is multiple regression analysis by testing the previous classic assumption test. While hypothesis testing is done by using the F test and t test. The results of the study prove that 1) Credit Risk (NPL) has a negative and significant effect on Profitability (ROA) of PT. Maha Bhoga Marga. 2) Liquidity Risk (LDR) has a positive and significant effect on Profitability (ROA) of PT. Maha Bhoga Marga. 3) Operational Risk (BOPO) has a negative and significant effect on Profitability (ROA) of PT. Maha Bhoga Marga.